Cholinergic modulation of auditory P3 event-related potentials as indexed by CHRNA4 and CHRNA7 genotype variation in healthy volunteers. (3rd June 2016) - Hyde, Molly; Choueiry, Joëlle; Smith, Dylan; de la Salle, Sara; Nelson, Renee; Impey, Danielle; Baddeley, Ashley; Aidelbaum, Robert; Millar, Anne; Knott, Verner
Highlights: CHRNA4C/C homozygotes show lower involuntary (P3a) and voluntary (P3b) attention. CHRNA7C/C homozygotes show lower voluntary (P3b) attentional processing. Mutations at the SLC5A7 gene did not significantly affect attention. Abstract: Schizophrenia (SZ) is a psychiatric disorder characterized by cognitive dysfunction within the realm of attentional processing. Reduced P3a and P3b event-related potentials (ERPs), indexing involuntary and voluntary attentional processing respectively, have been consistently observed in SZ patients who also express prominent cholinergic deficiencies. The involvement of the brain's cholinergic system in attention has been examined for several decades; however, further inquiry is required to further comprehend how abnormalities in this system affect neighbouring neurotransmitter systems and contribute to neurocognitive deficits. The objective of this pilot study was to examine the moderating role of the CHRNA4 (rs1044396), CHRNA7 (rs3087454), and SLC5A7 (rs1013940) genes on ERP indices of attentional processing in healthy volunteers ( N = 99; Caucasians and non-Caucasians) stratified by genotype and assessed using the auditory P300 "oddball" paradigm. Results indicated significantly greater P3a and P3b-indexed attentional processing for CT (vs. CC) CHRNA4 carriers and greater P3b for AA (vs. CC) CHRNA7 carriers. SLC5A7 allelic variants did not show significant differences in P3a and P3b processing. These findings expand our knowledge on the moderating effect of cholinergic genes on attention and could help inform targeted drug developments aimed at restoring attention deficits in SZ patients.